Mediterranean Type Diet Protects Adult Individuals From Diabetes - Uçar, Zeliha; Akman , Mehmet (Progress in Nutrition, 2021)
Objective: As one of the sustainable diets, the Mediterranean diet (MD) is one of the healthiest diets in the world. The aim of this study is to determine the effect of MD, which is one of the dietary models supporting healthy nutrition, on biochemical parameters in adult individuals. MD supports healthy life and is important in preventing chronic diseases. Methods: study was conducted with a total of 122 individuals between the ages of 18-64 who applied to Sakarya University Healthy Nutrition / Obesity Counseling Unit between September 2019 and February 2020. The data were collected by face-to-face interview technique. Collected data are; demographic information, Mediterranean diet compliance scale survey, and biochemical parameters. Results: According to the results obtained, the erythrocyte and fasting insulin in individuals were found to be significant with the Mediterranean diet compliance (p <0.05). Homeostatic Model Assessment-Insulin Resistance (HOMA-IR) and fasting insulin were found to be significant with Mediterranean diet compliance in the analyzes performed for women (p <0.05). Conclusion: As a result; The results obtained were determined that the Mediterranean diet was associated with some biochemical findings. The Mediterranean diet is thought to be effective in preventing diabetes and its accompanying macro and micro complications.